2020
DOI: 10.1039/c9ra10501h
|View full text |Cite
|
Sign up to set email alerts
|

High catalytic activity of CuY catalysts prepared by high temperature anhydrous interaction for the oxidative carbonylation of methanol

Abstract: The CuY catalysts prepared by high temperature anhydrous interaction were activated under different atmospheres and the activities were measured for the oxidative carbonylation of methanol to dimethyl carbonate under atmospheric pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…As a chlorine-free catalyst, Cu-exchange zeolite catalysts have attracted wide attention due to their high catalytic activity, especially the CuY zeolite catalyst [28][29][30]. CuY zeolites prepared by solid ion exchange, liquid-phase ion exchange, and initial wet impregnation showed significant differences in catalytic performance, which could be attributed to the differences in the presence of Cu in the zeolite (Cu+, Cu 2+ , Cu 2 O, and CuO) [29][30][31]. Although the influence of the Cu occurrence state on DMC yield was obtained through experimental preparation and characterization, the theoretical calculation provided a reasonable explanation.…”
Section: Catalyst For Methanol Gas-phase Oxidative Carbonylationmentioning
confidence: 99%
“…As a chlorine-free catalyst, Cu-exchange zeolite catalysts have attracted wide attention due to their high catalytic activity, especially the CuY zeolite catalyst [28][29][30]. CuY zeolites prepared by solid ion exchange, liquid-phase ion exchange, and initial wet impregnation showed significant differences in catalytic performance, which could be attributed to the differences in the presence of Cu in the zeolite (Cu+, Cu 2+ , Cu 2 O, and CuO) [29][30][31]. Although the influence of the Cu occurrence state on DMC yield was obtained through experimental preparation and characterization, the theoretical calculation provided a reasonable explanation.…”
Section: Catalyst For Methanol Gas-phase Oxidative Carbonylationmentioning
confidence: 99%
“…[15][16][17] The reducibility of the copper-containing zeolite Y samples is evaluated via TPR-H 2 . According to the literature, 18,19 Cu species in zeolites are reduced via two main reduction steps, the reduction of Cu 2+ to Cu + and the reduction of Cu + to Cu 0 . For instance, Wang et al 16 reported a reduction of isolated Cu 2+ to Cu + below 300 °C, and the reduction of CuO x to Cu 0 and Cu + ions to metallic Cu above 300 °C over copper-containing zeolite Y samples.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Among these methods, the one using vapor phase oxidative carbonylation of methanol has advantages over the others due to its low cost, easy access to feed materials, and simple and environmentally friendly production procedure. Extensive research has focused on DMC production by the vapor phase oxidative carbonylation of methanol, and catalysts play a crucial role in DMC production [ 5 , 6 , 7 , 8 , 9 , 10 ]. Different catalysts and their performances in DMC productions are listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%